2019
DOI: 10.1021/acs.nanolett.9b00313
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Nanoscale Redox Mapping Using Tip-Enhanced Raman Spectroscopy

Abstract: Electrochemical atomic force microscopy tip-enhanced Raman spectroscopy (EC-AFM-TERS) was used for the first time to spatially resolve local heterogeneity in redox behavior on an electrode surface in situ and at the nanoscale. A structurally well-defined Au(111) nanoplate located on a polycrystalline ITO substrate was studied to examine nanoscale redox contrast across the two electrode materials. By monitoring the TERS intensity of adsorbed Nile Blue (NB) molecules on the electrode surface, TERS maps were acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 52 publications
(85 reference statements)
0
58
0
Order By: Relevance
“…Due to strong hot electron doping through the plasmonic coupling between MoS 2 and Au nanoclusters, the TERS spectra indicated a structural change of MoS 2 from the 2H to the 1T phase. Using electrochemical atomic force microscopy, the TERS intensity maps represented well the spatially dependent redox behavior of Nile Blue on Au nanoplate on indium tin oxide electrode . Moreover, Raman intensity in TERS depends strongly on the incident light polarization .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Due to strong hot electron doping through the plasmonic coupling between MoS 2 and Au nanoclusters, the TERS spectra indicated a structural change of MoS 2 from the 2H to the 1T phase. Using electrochemical atomic force microscopy, the TERS intensity maps represented well the spatially dependent redox behavior of Nile Blue on Au nanoplate on indium tin oxide electrode . Moreover, Raman intensity in TERS depends strongly on the incident light polarization .…”
Section: Introductionmentioning
confidence: 93%
“…Combining the utility of scanning probe microscopy and Raman scattering, tip‐enhanced Raman spectroscopy (TERS) has become an ultrasensitive detection technique, and it is widely used in the fields of atomic structure, catalytic processes, and the redox behavior of single molecules . The selective Raman enhancement has been studied through the modifications and functionalization of TERS probes and controlling of surface plasmon polarizations and light polarizations . In order to break the limit of the scattering cross sections and reduce background noise, silver nanoparticles were employed as nanoantennas to couple free‐space excitation light to propagating surface plasmon polarizations in a sharp‐tip silver nanowire to excite Raman signals remotely .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] In recent years, heterostructural building blocks using 2D, one dimensional (1D) and zero dimensional (0D) materials have opened up unique opportunities for fundamental scientic studies due to the combined advantages of the individual materials. [6][7][8][9][10][11][12] Recent reports demonstrated that heterostructures exhibit exceptional optical and electronic properties that are not available in the individual material. [4][5][6][7][8][9][10] Due to its high sensitivity, nondestructive character and ngerprint identication capability, SERS is highly promising in biomedical technology.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] On the other hand, in the last few years SERS substrates based on two-dimensional (2D) transition-metal dichalcogenides (TMD) have been reported, where Raman intensity can be enhanced by $10 2 via CM as well as due to the resonance with near-and far-eld optical properties. 11,16,[20][21][22][23][24] To take the advantages of the EM and CM effect from both types of materials, in the current manuscript we have reported the development of novel heterostructure material-based SERS using 2D WS 2 TMD and 0D plasmonic gold nanoparticles (GNPs). The reported data show a remarkably high SERS sensitivity of $10 À10 to 10 À11 M from the heterostructure.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, TERS has been also combined with tip based electrochemical measurements demonstrating the correlation of complementary information. [ 15 ] Therefore, TERS is ideally suited to study the property‐function relation of polymer nano‐objects by revealing the chemical composition and structural differences based on the identification of certain marker bands and individual band positions. Several TERS studies have addressed thin films of polymer blends, [ 16–18 ] polymerization reactions, [ 19,20 ] and investigated structural modifications in certain biopolymers, such as fibrils.…”
Section: Introductionmentioning
confidence: 99%